Palladium-catalyzed para-selective alkylation of electron-deficient arenes - Jiao, Zhiwei (2019)
Intermolecular alkylations of electron‐deficient arenes proceed with good para selectivity. Palladium catalysts were used to generate nucleophilic alkyl radicals from alkyl halides, which then directly add onto the arenes. The arene scope and the site of alkylation are opposite to those of classical Friedel–Crafts alkylations, which prefer electron‐rich systems.